Konsep Kecerdasan Spiritual Dan Kecerdasan Emosional Persepektif Ibnu Athaillah As- Sakandari - Barlian Fajri (Tihamah: Jurnal Studi Islam, 2023)
The ongoing spiritual crisis has had significant consequences, especially in the form of "disorientation" in modern society. In this context, disorientation refers to a feeling of loss of direction and purpose in life, as well as a lack of clarity regarding the roots of human values and origins. This research is a type of library research, which adopts a qualitative approach with a descriptive-analytical focus. Sheikh Ibnu Athaillah did not specifically mention the meaning of spiritual intelligence in his works such as al-Hikam. However, from his explanation of spiritualism, it can be understood that spiritual intelligence is an effort to optimize the potential of human intelligence towards Allah SWT. according to Sheikh Ibnu Athaillah, however, it can be understood that the aim of emotional intelligence is to develop an individual's ability to understand, manage and express emotions well.